MEASUREMENT OF COOPERATIVE PERFORMANCE WITH THE BALANCE SCORECARD ANALYSIS APPROACH - Soffia Pudji Estiasih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to determine and analyze the Balance Scorecard approach as a measurement the performance of the Republic of Indonesia Employee Cooperative at “Kopertis” Region VII in Surabaya. The Balance Scorecard approach takes into account financial and non-financial aspects that are neglected by traditional performance measurements. Data collection was carried out by interview method with related sections and documentation. The data analysis technique used a qualitative descriptive method with a Balance Scorecard approach through 4 perspectives, namely a financial perspective, a customer perspective, an internal business process perspective and a learning and growth perspective. The results indicate that the measurement of cooperative performance in terms of 4 perspectives as a whole is good; this is indicated by a total score of 9 for financial, customer and learning & growth perspectives, obtaining good scores and a total score of 3 for internal business process perspectives obtaining sufficient scores. The conclusion that can be drawn is that the measurement of performance in cooperatives is more comprehensive. The suggestion proposed is the “Kopertis” Region VII Civil Servant Cooperative in measuring performance using the Balance Scorecard in order to find out the potential that the cooperative has for the welfare of all members.